Simultaneous Massive Esophageal Mucosal Candidiasis and Profound Cytomegaloviral Esophageal Ulcers with Recurrence of Both Infections 12 Years Later in a Patient with Long-Standing AIDS: Endoscopic, Radiologic, and Pathologic Findings. (27th February 2022) - Gill, Inayat; Edhi, Ahmed; Amin, Mitual; Cappell, Mitchell S.
Abstract : Immunocompromised patients with acquired immunodeficiency syndrome (AIDS) can develop opportunistic esophageal candidial and cytomegaloviral infections. A case is reported which extends the clinico-endoscopic severity of these infections. A 32-year-old bisexual man with AIDS since 1997, and intermittently compliant with antiretroviral therapy, presented (2007) with dysphagia and 32 kg-weight loss. EGD revealed a massive, cheesy, esophageal mucosal exudate from Candida albicans . Cytomegalovirus was isolated by viral culture. The patient improved after fluconazole/ganciclovir therapy. The patient re-presented (2019) with hematemesis and dysphagia. EGD revealed cheesy esophageal exudate and profound "punched out" esophageal ulcers mimicking pseudo-diverticula. Histopathology confirmed candidiasis. Viral cultures revealed cytomegalovirus. Barium esophagram revealed deep esophageal ulcers/pseudo-diverticula. Repeat EGD 8 weeks later after ganciclovir/micafungin therapy revealed mostly healed lesions. This demonstrates that AIDS patients may have massive mucosal esophageal candidiasis; that both infections can recur years after apparent eradication; and that cytomegaloviral esophageal ulcers may be profound and mimic pseudo-diverticula. A comprehensive literature review revealed only one abstract of esophageal pseudo-diverticula associated with cytomegalovirus. Simultaneous esophageal candidial and CMV infections have also been rarely reported in immunocompromised patients without AIDS.